Peripheral neuropathy in patients with myotonic dystrophy type 1. (1st May 2013) - Peric, Stojan; Stojanovic, Vidosava Rakocevic; Nikolic, Ana; Kacar, Aleksandra; Basta, Ivana; Pavlovic, Sanja; Lavrnic, Dragana
<x xml:space="preserve">Abstract</x> Objectives: To assess the frequency and type of peripheral neuropathy (PNP) in patients with myotonic dystrophy type 1 (DM1), as well as to identify factors that may be associated with this abnormality. Methods: This study comprised 111 adult patients with DM1. Nerve conduction study was performed on sural, peroneal and median nerves of both limbs. Results: PNP was somewhat more frequent in DM1 patients with glucose intolerance and diabetes mellitus (66·7 vs 33·7%, P = 0·05). In DM1 patients with no glucose intolerance, diabetes mellitus and thyroid dysfunction, the most frequent type of PNP was demyelinating (70·0%) and motor (83·3%). PNP was more frequent in males (45·7 vs 20·9%, P<0·05). Patients with PNP were older (43·7±7·3 vs 39·6±9·6 years, P<0·05) and had a longer duration of DM1 compared to those without PNP (18·6±9·9 vs 12·7±8·3 years, P<0·01). DM1 patients with PNP had a higher body mass index) (24·9±5·5 vs 22·4±4·2 kg/cm2, P<0·05), higher triglycerides (3·1±3·3 vs 1·8±0·8 mmol/l, P<0·01), total cholesterol (6·2±1·4 vs 5·4±1·1 mmol/l) and LDL cholesterol (4·3±1·2 vs 3·4±1·0, P<0·05). Achilles reflexes were absent in 76·9% patients with PNP and in 51·9% patients without PNP (P<0·05). Patellar reflexes and muscle strength were similar in both groups (P>0·05). Conclusions: PNP was present in one-third of DM1 patients. The most common type was motor and demyelinating PNP. Our results suggest the association between the presence of peripheral nerve impairment in DM1 and male gender, age, duration of disease and certain metabolic parameters.